2021
DOI: 10.37708/psyct.v14i1.578
|View full text |Cite
|
Sign up to set email alerts
|

Do Ego-Resiliency, Self-Efficacy and Life Orientation Predict Self-Esteem of Top World Magicians? An International Study

Abstract: Performing as an illusionist requires having adequate internal and personality resources. These determine the success of stage performance and have an impact on how an individual perceives self, and influence the self-esteem. The aim of the article is to determine how ego-resiliency, self-efficacy, and optimism influence the self-esteem of top-world magicians. A group of 50 top world magicians – world champions of magic – took part in the research. The participants were surveyed using the Self-Esteem Scale (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Researchers found post-intervention scores to be lower for magic than for drawing, which is difficult to explain without baseline measures but may simply be confounded by the beneficial aspects of the drawing activity. The relationship to self-esteem exists amongst professional magicians, with self-esteem being correlated with self-efficacy, ego-resiliency, and optimism (Napora, 2021).Taken altogether, magic tricks show promise, yet some results are mixed, thus requiring high quality experiments to clarify their impact on self-esteem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers found post-intervention scores to be lower for magic than for drawing, which is difficult to explain without baseline measures but may simply be confounded by the beneficial aspects of the drawing activity. The relationship to self-esteem exists amongst professional magicians, with self-esteem being correlated with self-efficacy, ego-resiliency, and optimism (Napora, 2021).Taken altogether, magic tricks show promise, yet some results are mixed, thus requiring high quality experiments to clarify their impact on self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding self-esteem, prior experiments have typically involved younger participants learning and performing magic, especially in populations with low self-esteem. The majority of studies examining self-related constructs from learning magic found a positive impact (Ezell & Klein-Ezell, 2003; Fancourt & Poon, 2016; Lustig, 1994; Napora, 2021; Spencer, 2012). Two studies had inadequate statistical power, only revealing numerical increases in self-esteem scores (Kwong & Cullen, 2007; Levin, 2006) while one study had nonsignificant results (Sui & Sui, 2007).…”
mentioning
confidence: 99%
“…65 By performing acts considered impossible by others before an audience and receiving enthusiastic applause, participants gained self-efficacy, 43 a predictor of self-esteem for magicians. 66 Finally, performing magic for family members and friends after the course further enhanced participants' self-confidence, sense of accomplishment, and interaction with others. Audience interaction is a crucial aspect of magic performance, 67 and increased relational value and social acceptance can lead to higher self-esteem.…”
Section: Discussionmentioning
confidence: 96%
“…At the level of performing magic, participants gained unique knowledge and skills in performing magic tricks, positively impacting global self‐esteem 65 . By performing acts considered impossible by others before an audience and receiving enthusiastic applause, participants gained self‐efficacy, 43 a predictor of self‐esteem for magicians 66 . Finally, performing magic for family members and friends after the course further enhanced participants' self‐confidence, sense of accomplishment, and interaction with others.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a tendency in research focusing mainly on cognitive psychology (Barnhart, 2010;Beth & Ekroll, 2014;Kuhn, 2019;Macknik & Martinez-Conde, 2010). There is less published research which focuses on the link between magic and well-being (Wiseman & Watt, 2018) or personality and internal resources of magicians (Napora & Sękowski, 2020;Napora, 2021). The motivation of the research is the willingness to provide new knowledge about the functioning of illusionists in terms of their sense of quality of life.…”
Section: Introductionmentioning
confidence: 99%